Landfill leachate treatment by combination of electro - fenton and sequencing batch reactor method - Muhamad Hanafi, Nur Fatihah (2015)
Landfill leachate contains a large amount of organic, inorganic and heavy metal contents. Untreated leachate is a potential source to effect of soil, surface and groundwater. The combined treatment offers an alternative technique in dealing to leachate treatment. This research is to determine the effectiveness of combined electro-Fenton and sequencing batch reactor (SBR) method on the removal of SS, colour, COD and NH3-N. The experimental involved three major parts were coagulation-flocculation, electro-Fenton and SBR method. This process could be operated independently in a batch mode and optimum conditions for each treatment were identified. In the combined process, leachate was first fed to coagulation-flocculation for pre-treatment. Then, the effluent from that process was oxidized in electro-Fenton process. The final process is the effluent of leachate was fed to a SBR method. The combined treatment was operated under the optimum conditions for all the processes. The result of coagulation-flocculation shown PAC is more effective at 2500 mg/L of optimum dosage. After coagulation-flocculation process, the removal of SS, colour, COD and NH3-N were 80%, 77%, 61% and 35% respectively. The result of electro-Fenton shown Al-Al is more effective at 200 A/m2 of optimum current density, 25 minutes of optimum reaction time, 4 of optimum pH, 800 mg/L of optimum H2O2 dosage and 1000 mg/L of optimum FeSO4•7H2O dosage. After electro-Fenton process, the removal of SS, colour, COD and NH3-N were 87%, 95%, 82% and 65% respectively. The final process of SBR effluent was approaching neutral pH at 6.90 at 2800 mg/L of optimum MLSS and 6 h of optimum reaction time. The overall performance of combined treatment on the removal of SS, colour, COD and NH3-N were 84%, 82%, 87% and 78% respectively. Thus, this combined treatment offers as an alternative technique for landfill leachate treatment on the removal of pollutants.